Differences in ride-hailing adoption by older Californians among types of locations - Shirgaokar, Manish; Misra, Aditi; Weinstein Agrawal, Asha; Wachs, Martin; Dobbs, Bonnie (Journal of Transport and Land Use, 2021)
Ride-hailing services such as Lyft and Uber can complement rides offered by family, friends, paid providers, and public transit. To learn why older adults might wish to use ride-hail, we conducted an online survey of 2,917 California respondents age 55 and older. Participants were asked whether they would value four features hypothesized to be benefits of ride-hailing. We specified binary logit models and used market segmentation to investigate whether there were location-based differences in the use of ride-hailing. Our analysis showed that women, city dwellers, persons with disabilities, and those who rely on others for rides were more open to ride-hailing. Women in suburbs or small town/rural settings were more likely to ride-hail than their male counterparts for reasons of independence, fear of being lost while driving, or getting help with carrying bags. Urban women, in contrast, were less likely than their male counterparts to ride-hail for these reasons. High-income individuals in suburbs or small town/rural locations were more likely to ride-hail than low-income respondents, while high-income urban residents were less likely to ride-hail. Adoption of ride-hailing services and the reasons for doing so showed strong variability by location even among respondents with similar socio-demographic attributes.